Breath of Light: Towards Reclaiming Shared Breathing through a Meditative Installation - Liu, Pinyao; Desnoyers-Stewart, John; Stepanova, Ekaterina R.; Riecke, Bernhard E. (Leonardo, 2023)
Breath of Light is an immersive breath-responsive installation aiming to reclaim the connective nature of sharing breath in public spaces. During the exhibition at the 13th Shanghai Biennale in March 2021, the lead author observed and interviewed participants to better understand their experience. A subsequent follow-up interview was conducted in January 2023 to understand the long-term effect. This technological mediation of breathing explores its transformative potential to revive the connective connotations of shared breathing, and cultivate interoceptive awareness, reflection and inter-human connection during the pandemic and beyond, with the use of breathing interaction, metaphors, symbols, and ambiguous instructions.
Keywords: Riecke_2023; bernhard-riecke; breath-of-light; john-desnoyers-stewart; journalPaper; katerina-stepanova; pinyao-liu; proj -- breath-of-light; proj--breath-of-light; thesis-related